Legal Implications Of Mining Business Licensing Policies For Community Organisations In The Religious Sector - Al'anam, Muklis; Ledy Diana (Magister Ilmu Hukum Fakultas Hukum Universitas Riau, 2025)
Through this study, the author explores the challenges and potentials that arise from granting mining licences to religious organisations, including potential conflicts between economic objectives and moral values held by religious organisations. On the one hand, mining activities can provide economic opportunities for religious organizations and neighbouring communities, but on the other hand, these activities risk damaging the environment and contradicting religious teachings that prioritise nature conservation. The article also identifies the importance of clear policies and strict supervision to ensure that mining activities by religious organisations are not only financially beneficial but also socially and environmentally responsible. Thus, this research uses a normative method to seek truth coherence, with a statutory approach, conceptual approach and case approach. In conclusion, this article recommends the need for stricter regulations, transparency in the licensing process, as well as strengthening dialogue between the government, religious organisations and the community to ensure the sustainability of these activities in line with existing religious and social values.